Exploring Dengue Dynamics from a Multi-dimensional Surveillance Approach: A Cross-sectional Study from Maharashtra, India - Rina Tilak; Suraj Kapoor; Vivek Anand; Swati Bajaj; Kunal Koundinya; Arun Yadav (Preventive Medicine: Research & Reviews)
Introduction: The epidemiology of dengue in India has been intricate. It is pertinent that the multidimensional dengue surveillance approach be formulated with appropriate inferences and implications in developing preventive strategies for dengue control. Materials and Methods: This was a cross-sectional study from Pune city in Western Maharashtra in July 2021, covering an area of 120 acres and population of 3234. A multidimensional dengue field survey was conducted to carry out sector-wise entomological surveillance with simultaneous knowledge and behaviour assessment of the local population. Results: The total number of dengue cases reported were 36 over 2 months. A total of 131/973 containers were found positive, with a total collection of 1140 larvae and 119 pupae. Pupa per person was 0.16. A total of 108 adult female Aedes mosquitoes majorly Aedes albopictus (84%). The xenodiagnoses undertaken were found negative for dengue, chikungunya and Zika virus. The mean knowledge behaviour score assessed was 8.64 ± 2.12 out of 14 with a maximum score of 14 and a minimum score of 02. Conclusion: The current study revealed that there were specific preferred breeding sites such as plastic discarded plates and flowerpots with more cases in particular sector. The knowledge assessment of the local population was good.